Generation of non-transgenic iPS cells from human cord blood CD34 + cells under animal component-free conditions - Alexandra Haase; Gudrun Göhring; Ulrich Martin (2017)
Recently, many hurdles and limitations for production of clinically applicable iPSC derivatives have been overcome. Transgene-free iPSCs can be efficiently derived from easily accessible cell sources such as blood. Here we describe the generation of transgene-free hiPS cells from cord blood derived CD34+ cells, reprogrammed using CytoTune™ Sendai reprogramming vectors. CD34+ cell isolation, cultivation, reprogramming and establishment of resulting hiPSC lines were performed under the exclusive usage of animal-derived component-free (ADCF) materials and components.